Pengaruh Current Ratio (CR) Dan Debt To Asset Ratio (DAR) Terhadap Return On Asset (ROA) Pada PT Astra Agro Lestari Tbk Periode 2015-2024 - Ina Lisa Astuti; Bulan Oktrima (CV. KAMPUS AKADEMIK PUBLISING, 2026)
partially and simultaneously on Return On Assets (ROA) at PT Astra Agro Lestari Tbk for the 2015-2024 period. The research method used is quantitative with an associative approach. The population in this study employs SPSS version 25, wich includes classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), multiple regression tests, correlation coefficient tests, coefficient determination tests, and hypothesis tests (t-test and F-test). Based on the partial test results, the Current Ratio has ni significant effect on Return On Assets, as indicated by the value of Tcount < Ttable or |-1,600| < (2,364) with a Sig. value of 0,154 > 0,05. Based on the pertial the reasults, the Debt to Asset Ratio also has no significant effect on Return On Assets, as indicated by the value of Tcount < Ttabel or |-1,401| < (2,364) with a Sig. value of 0,204 > 0,05. However, based on the simultaneous test results, both variabels the Current Ratio and Debt to Asset Ratio do not have a significant effect on Return On Assets, as indicated by the value of Fcount < Ftable or (1,582) > (4,74) with a Sig. value of 0,271 > 0,05.